Separación y su incidencia en la estabilidad emocional de un individuo de 30 años de edad del cantón Milagro - Peralta Macias, Neyshi Noemi (2022)
The present case study was carried out with the objective of analyzing the separation of a couple and its influence on the emotional stability of a 30-year-old individual from the Milagro canton, the qualitative methodology used in this work is aimed at determining the variables such as : Separation and emotional stability which are exposed in the present case study, also thanks to the implementation of the REBT techniques, it was possible for the stated objective to be fulfilled in its entirety, all this was carried out through a therapeutic plan on which contemplates an Individual Therapy procedure, aimed at modifying those irrational beliefs that the patient manifested during the psychological intervention, in this way it was possible to mitigate the symptoms in the 30-year-old individual due to the love break, in this way it was achieved great results in improving their quality of life, both personal and social.